La psicomotricidad y su influencia en el desarrollo integral y académico de las niñas del segundo grado del primer nivel de educación general básica de la escuela “Ciudad de Loja” del cantón y provincia de Loja, año lectivo 2012-2013 - Sarmiento Calva, Nelly Elizabeth (2014)
The present investigation called THE PSICOMOTRICIDAD AND THEIR INFLUENCE IN THE INTEGRAL AND ACADEMIC DEVELOPMENT OF THE GIRLS OF THE SECOND GRADE OF THE FIRST LEVEL OF BASIC GENERAL EDUCATION OF THE SCHOOL “CIUDAD DE LOJA” OF THE CANTON AND COUNTY DE LOJA, YEAR LECTIVO 2012-2013;For that which thought about the following general objective, to know the psicomotricidad and their influence by means of the investigation to elevate the integral and academic development of the girls of the second grade of the first level of Basic general Education of the school “City of Loja”, to determine if the development of the psicomotricidad impacts in the school yield. The specific objectives were projected to investigate if the integral development of the children depends on the application of the psicomotricidad and to verify if the educational ones put into practice the psicomotricidad techniques. Likewise he/she thought about the following methods: scientific, descriptive, analytic, deductive, statistical, the same ones that were fundamental for the bibliography revision, analysis and interpretation of surveys and other investigation parameters; the technique of the survey was used to achieve bigger certainty of the reality on the psicomotricidad and its influence in the integral and academic development of the girls. The results are described according to each objective, what allowed knowing the good development of the psicomotricidad in the students of the second grade that it impacts in the integral and academic development. With the application of technical and investigative instruments as the surveys that were applied the whole taken population as relating, 7 educational and 79 students in this investigation and by means of the poll you could evidence and to analyze the obtained information to be able to verify the existent problem in this institution. For the presentation of results, you proceeded by means of the deductive and descriptive method; reaching the conclusion that the educational ones in their majority have a clear knowledge on what is the psicomotricidad, is aspired that with this investigation, you can reinforce even more the psicomotricidad concept for a good integral and academic development of the students.